2020
DOI: 10.1371/journal.pone.0244188
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of dyads in social life

Abstract: A salient objective feature of the social environment in which people find themselves is group size. Knowledge of group size is highly relevant to behavioural scientists given that humans spend considerable time in social settings and the number of others influences much of human behaviour. What size of group do people actually look for and encounter in everyday life? Here we report four survey studies and one experience-sampling study (total N = 4,398) which provide evidence for the predominance of the dyad i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 59 publications
(76 reference statements)
1
15
0
Order By: Relevance
“…In a large study of Facebook friendships, David-Barrett et al (2015) found evidence consistent with women preferring same-sex dyadic relationships and men favoring larger, samesex cliques. Similarly, an experience-sampling study of Dutch and American participants found that women engaged in collective activities in dyads more than men (Peperkoorn et al, 2020). In addition, studies of same-sex groups suggest boys and men tend to organize their groups hierarchically more than women, whereas women are more likely to enforce egalitarianism (Benenson & Abadzi, 2020;Berdahl & Anderson, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In a large study of Facebook friendships, David-Barrett et al (2015) found evidence consistent with women preferring same-sex dyadic relationships and men favoring larger, samesex cliques. Similarly, an experience-sampling study of Dutch and American participants found that women engaged in collective activities in dyads more than men (Peperkoorn et al, 2020). In addition, studies of same-sex groups suggest boys and men tend to organize their groups hierarchically more than women, whereas women are more likely to enforce egalitarianism (Benenson & Abadzi, 2020;Berdahl & Anderson, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to women, men may have also experienced greater selection to engage in rapid, large-scale coalition-building, for purposes of often violent aggression (Wrangham and Peterson, 1996). Perhaps consistent with this claim is evidence, at least in WEIRD populations, that men can be more likely to build larger social networks with more "weak" ties (Vigil, 2007;Seabright, 2012;Friebel et al, 2017), prefer socializing in larger same-sex groups (David-Barrett et al, 2015;Benenson, 2019;Peperkoorn et al, 2020), and organize their groups hierarchically while revering other group members' competitiveness (Berdahl and Anderson, 2005;Watkins and Jones, 2016;Benenson and Abadzi, 2020). One general interpretation of the foregoing is that men and women may have evolved different, though overlapping, political strategies, where for men within-group cooperation may be more beneficial for enhancing between-group competition, while for women, within-group cooperation is likely to be more circumscribed and focused on recruiting sources of stable social support (Vandermassen, 2008;Mcdonald et al, 2012).…”
Section: Evoluɵonary Historymentioning
confidence: 80%
“…This includes men's greater tendency for self-promotion, overconfidence and exaggerating their competence, which helps elevate many unqualified men to positions of power (Chamorro-Premuzic, 2019). To the extent men, more than women, prefer to socialize in larger same-sex groups (Low, 1992;David-Barrett et al, 2015;Benenson, 2019;Peperkoorn et al, 2020) and to build larger social networks comprised of many "weak" ties (Vigil, 2007;Seabright, 2012;Friebel et al, 2017), men may be unduly privileged in the pursuit of leadership, particularly in the mixed gender hierarchies of large organizations (van Vugt and Spisak, 2008;Cullen-Lester et al, 2016;Lindenlaub and Prummer, 2020). Effects of social networking on gender differences in leadership are exacerbated when leaders tend to be male and leaders in general prefer to hire and promote similar others (i.e., the "old boys network") (McDonald, 2011;Koch et al, 2015).…”
Section: Some Implications For Policymentioning
confidence: 99%
“…Many everyday activities involve more than one actor at once, and groups of interacting co-actors have different size. Especially, interactions between two humans (so-called dyadic interactions) are the most prevalent in social settings (Peperkoorn et al, 2020 ). During such situations, we spend most of our time trying to coordinate our behavior and actions with other humans.…”
Section: Introductionmentioning
confidence: 99%